The pandemic as an opportunity to reflect on athletic training research - Driban, J. B.; McKeon, P. O. (International Journal of Athletic Therapy & Training, 2021)
As we emerge from the COVID-19 pandemic, the athletic training community needs to reflect on the pandemic`s impact on athletic training research. This reflection requires the athletic training community to consider how studies were and will be affected, how investigators deliver research messaging to stakeholders, how editors and reviewers assess research, and how investigators` careers were impacted. We wish we could offer some grand proposal for how to address these critical questions. Instead, we seek to encourage an era of reflection on how athletic trainers do research, assess research, disseminate research, and who is involved in research. The athletic training community should use the pandemic as a once in a century temporal landmark to elicit a "fresh start effect." It can become an opportunity "to relegate past imperfections to a previous period, induce people to take a big-picture view …, and thus motivate aspirational behaviors." We offer topics for key stakeholders (e.g., authors, readers, editors, mentors, reviewers) to consider, and some immediate action items that should be implemented as the discussion evolves.